Beyond Discovery Learning: The Impact of the Mordiscvein Model on Students’ Critical Thinking Skills in Biology - Raicha Oktafiani; Aryani Dwi Kesumawardani; Yoga Aditya Saputra; Muhammad Farhan Barata (Pro-Life, 2026)
Critical thinking skills are essential competencies for students in the 21st century; however, conventional instructional models such as discovery learning often fail to optimally foster students’ engagement in higher-order thinking processes. This study examined the effect of the Mordiscvein learning model on senior high school students' critical thinking skills in biology compared with the discovery learning model. A quasi-experimental design with a non-equivalent control group was employed involving 72 tenth-grade students (36 experimental, 36 control) at a public senior high school in Bandar Lampung, Indonesia. The intervention was conducted over four weeks (eight 90-minute sessions). Data were collected using a 10-item essay-based critical thinking test covering analysis, inference, and evaluation indicators, with acceptable reliability (Cronbach's α = 0.82). The results indicated that students taught using the Mordiscvein model achieved significantly higher posttest scores than those in the discovery learning group. Improvements were observed across all critical thinking indicators, suggesting that structured inquiry stages problem orientation, collaborative inquiry, guided experimentation, data interpretation, and reflective discussion—contribute to deeper cognitive engagement. These findings indicate that integrating systematic scaffolding into constructivist learning environments can more effectively support the development of critical thinking in biology education.